Paper-Based Characteristics of Banana Trunk (Musa Paradisiaca) and Waste Paper - Nova Suriani; Ainun Rohana; Nazif Ichwan (Jurnal Rekayasa Pangan dan Pertanian, 2014)
It is time for Indonesia to reduce dependence on using paper with tree raw materials. It can be an alternative environmentally friendly paper and does not increase the cut down of trees. The making of paper using the trunk of banana (Musa paradisiaca) and waste paper is suitable to overcome the problems of the use of the current paper. This research was done on May-Juni 2013. The paper making was done at Jl. Roso. No. 8 Delitua Medan North Sumatra and the testing of paper was done in PT PDM Indonesia, Laboratory Medan, using non-factorial randomized block design with one factor.i.e. waste paper composition (0%, 10%, 20%, 30%, 40% and 50%). Parameters observed were grammage, tensile and tearing strength. The results showed that the composition of the waste paper had highly signifficant effect on grammage and tensile strength. The resulting paper could be categorized as art paper with the best result of grammage was at the composition of 30% (350 g banana trunk and 150 g waste paper), and tensile strength and tearing strength at the composition of 0% (500 g banana trunk). Keywords: banana trunk, pulp composition, paper, waste paper